Freedom moves hip hop knowledges, pedagogies, and futures - Alim, H. Samy ca. 20./21. Jh; Chang, Jeff; Wong, Casey Philip (University of California Press, 2022)
"Moving through over a dozen cities across four continents, Freedom Moves: Hip Hop Knowledges, Pedagogies, and Futures represents a cutting-edge, field-defining moment in Hip Hop Studies. As we approach 50 years of hip hop cultural history, and 30 years of hip hop scholarship, hip hop continues to be one of the most profound and transformative social, cultural, and political movements of the late 20th and early 21st centuries. In this book, H. Samy Alim, Jeff Chang, and Casey Philip Wong invite us to engage dialogically with some of the world's most innovative and provocative Hip Hop artists and intellectuals as they collectively rethink the relationships between Hip Hop knowledges, pedagogies, and futures.
Keywords: Geschichte; Rap; Hip-Hop; Rap (Music) / Political aspects; Rap (Music) / Social aspects; Rap musicians / Political activity; Hip-hop / Influence; Rappeurs / Activité politique; Aufsatzsammlung